Induced‐transparency in silicon‐on‐insulator based novel resonator systems. (1st October 2013) - Cui, Danfeng; Wei, Liping; Liu, Chao; Liu, Yaoying; Wang, Yonghua; Liu, Jun; Xue, Chenyang
Abstract : The coupled‐resonator‐induced‐transparency (CRIT) phenomenon in a novel optical resonator system is experimentally demonstrated. The system is composed of a four‐ring resonator with a 20 μm diameter on silicon, whose spectrum has a narrow transparency peak with low group velocity. The CRIT effect is observed in the optical coupled‐resonator because of classical destructive interference. In this reported work, a CRIT resonance with a quality factor of 7.2 × 10 4 is demonstrated with the same cavity size and the power coupling of the system is 60%, which agree well with the theoretical analysis. Then, through and drop transmission spectra of the resonator coincide well with each other. Simultaneously, the detuning resonant wavelength can be controlled by changing the temperature.